Evaluation of Lumbar Spine Injuries on Computed Tomography - Ameena Ramzan, Taiba Zulfiqar, Abid Ali, Khadija Bakhtawar (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To use computed tomography to examine the findings of lumbar spine trauma. Material and methodology: This cross-sectional study which was performed with a sample size of 50 patients in 6 months from October-2022 to march-2022 calculated via a convenient sampling technique by taking the mean from previously published studies. This study was carried out at 3 private hospitals in Sialkot, Pakistan after informed consent. Data were statistically analyzed using SPSS version 20. Frequency and percentages were mentioned. Results: Mostly patients were male 27(54%) and the least number of patients were females 23(43%). The most frequent age group was 55-65 years15 (30%). The most frequent weight was 66-75kg 20(40%) and the lowest weight was 46-55kg 8(16%). There is a high risk of lumber spine trauma in overweight patients. The most frequent type was simple 30(60%) and the least type was comminuted 5(10%). the most frequent findings were mild 30(60%) Single vertebral fracture 36(72%) is most common. L1 12(24%) was most common affected. Conclusion: Males have a higher incidence than females, with males. Vertebra number one is more influenced than the others in terms of the number of affected vertebrae. Simple fractures are the most common type of fracture. CT examination is best for evaluating lumbar spine injuries. Keywords: Computed tomography, Lumbar, Spine, Trauma